(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In this article, the causes of genetic diseases, factors of origin, diagnosis of the disease and their advantages and disadvantages in the use of anthropogenetic methods in this process are discussed.